Costs, quality, and competition in the cocoa value chain in Peru , an exploratory assessment - Scott Gregory J.; Donovan Jason; Higuchi Angie; Universidade Federal Rural de Pernambuco (UFRPE)
El valor total de las exportaciones de cacao desde Per ͠durante las l͠timas dos dčadas aument ̤de menos de US